Mobile Learning Revolution: Harnessing the Potential of Smartphones in the Learning Process - Purnama, Yulian; Lewa, Inriati; J, Syilvia Wenny; S, Fauza Afni; Wahyuni, Sri (Journal International of Lingua and Technology, 2024)
Utilizing smartphone-based mobile learning in the learning process will provide the latest innovative alternatives to the learning process. Today's students tend to experience distractions in their learning process. Not infrequently the learning system that applies in a school makes students bored and not enthusiastic about learning. This could have been because the school did not make any changes in the existing education system. Where the effect of the incident will cause students to feel bored and bored in the learning process. In this era of the mobile revolution, it will create various advances in the field of technology that can be used to support the learning process. The purpose of this research is to find out the potential utilization of smartphones as a form of mobile learning revolution in the learning process. Through research on the Mobile Learning Revolution: Utilizing the Potential of Smartphones in the Learning Process, researchers hope that by utilizing the potential of smartphones as a manifestation of the mobile learning revolution in the learning process, it can facilitate the learning process itself. The method used in this research is a quantitative method. The researcher conducted a survey using the Google form which consisted of 15 statements related to the research title. Researchers found that the use of the potential of smartphones in the era of the mobile learning revolution had a major impact on the learning process. The existence of a smartphone in the learning process greatly facilitates the implementation of the teaching and learning process in schools. The limitations of this study are that researchers only conduct research in schools and researchers do not conduct research directly at schools but share survey links on Google forms containing statements about the Mobile Learning Revolution: Utilizing the Potential of Smartphones in the Learning Process.